China's Arctic Ambitions and What They Mean for Canada (2018)
With the possible exception of Russia, there is no country whose Arctic ambitions are viewed with more apprehension in the Western world than China. Wealthy and increasingly assertive, China’s interest in the region’s resources is growing, raising the spectre of a powerful communist dictatorship controlling strategically vital elements of the circumpolar economy. Since the early 1990s, the rapid growth of Chinese industry has transformed the country from a net exporter of raw materials into the world’s largest importer, a transition that resulted in the formation of some of the world’s largest stateowned mining and oil companies, which were sent overseas to secure new reserves. Over the past decade, these state-owned enterprises (SOEs) have spent billions establishing themselves as leaders in global resource extraction. 2013 alone, China’s overseas resource investments soared to $53.3 billion, up from $8.2 billion in 2005, and a rapidly growing percentage of this investment is being funnelled into the Arctic. The attraction is obvious: the circumpolar region is one of the last, largely undeveloped regions in the world and is purported to hold a significant share of the planet’s remaining minerals, oil, andgas. In the years to come this investment will almost certainly increase and China’s role in northern development will become even more pronounced. In spite of this, China’s role in Arctic resource development should not be exaggerated. China has been cautious in moving forward on risky Arctic venturesand many of Chinese-owned projects have stalled in the face of low resource prices. This chapter examines China’s growing interest and investment in Arctic resources and places these activities into context to show the role and intent of Chinese companies, and to demonstrate that popular fears of a “resource grab” are largely unfounded.